Isocitrate dehydrogenase mutation as a therapeutic target in gliomas - Han, Catherine H.; Batchelor, Tracy T. (Chinese Clinical Oncology, 2017)
Isocitrate dehydrogenases (IDH) are important enzymes that catalyze the oxidative decarboxylation of isocitrate to α-ketoglutarate (α-KG), producing NADPH in the process. More than 80% of low-grade gliomas and secondary glioblastoma (GBM) harbor an IDH mutation. IDH mutations involve the catalytic pocket of the enzyme and lead to a neomorphic ability to produce 2-hydroxyglutarate (2HG) while oxidizing NADPH to NADP+. 2HG is considered as an ‘oncometabolite’ which is thought to be responsible for many, if not all, biologic effects of IDH mutations. 2HG accumulation competitively inhibits α-KG-dependent dioxygenases, including histone lysine demethylases and DNA demethylases, resulting in a hypermethylation phenotype with alterations in cellular epigenetic status as well as a block in cellular differentiation. IDH mutations have been suggested as an important early event in tumorigenesis, however it remains unclear whether IDH mutation by itself causes cancer or if it requires other oncogenic events to initiate tumorigenesis. Significant efforts have been made to better understand the mechanisms of IDH mutations in tumor initiation and progression, and to develop targeted therapies for IDH-mutated tumors. This review provides an overview of the function of mutant IDH, and the current understanding of the role IDH mutations play in gliomagenesis. In addition, several potential therapeutic strategies for IDH-mutant gliomas, including mutant IDH inhibitors which have entered clinical evaluation in glioma patients, will be discussed.